(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: AIDS is a fatal illness that breaks down the body’s immune system, leaving the victim vulnerable to lifethreatening opportunistic infections, neurological disorders or unusual malignancies, having no effective treatment till now. Objectives: To assess the awareness and misconception about the transmission of HIV/AIDS among the troops of Bangladesh Army. Materials and Methods: This cross-sectional study was conducted from September 2011 to December 2011 among purposively selected 125 troops of various Army units of Dhaka Cantonment, Bangladesh. Data were collected by face-to-face interview by pretested structured questionnaire and analyzed by software SPSS version 17.0. Results: Among the 125 respondents, most (92%) of them were aware of the transmission of HIV/AIDS and having no significant misconception of its transmission. No association has been found between knowledge of HIV transmission and type of occupation. Conclusion: Most of the troops of the Bangladesh Army were aware of the transmission of HIV/AIDS and misconception among them was very less. The authority should continue thus status for the betterment of the country. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 180-182